Design of self-healing styrene-butadiene rubber compounds with ground tire rubber-based reinforcing additives by means of DoE methodology - Karina C. Nuñez Carrero; Luis E. Alonso Pastor; Marianella Hernández Santana; José María Pastor (Materials & Design, 2022)
In the effort to find a balance between the mechanical properties of self-healing styrene-butadiene rubber (SBR) compounds, before and after a macroscopic damage, a study based on the use of devulcanised tire residue (dGTR) as reinforcement has been carried out. Two full factorial designs and their analysis of variance (ANOVA) were used to overcome the challenge of relating the multiple microstructural variables of dGTR to the mechanical properties of the compounds in pristine and healed states. The design of experiments (DoE) predict that the use of dGTR-based reinforcements, with a decrease in network density higher than 50%, enables the incorporation of more than 40 phr of reinforcing filler, increasing the tensile strength in the pristine state (more than 4 times) and mitigating its negative effect on the healing process. Experimental tests have validated these theoretical predictions. This research demonstrates that it is not necessary to control the selectivity of the devulcanisation process. Therefore, it has been demonstrated that only by increasing the dGTR surface network density breakage it is possible to incorporate significant amounts of the residue from simple recycling processes in order to improve the performance of high value-added rubber formulations, such as self-healing materials.